DNA methylation in the norepinephrine transporter gene promoter region is not associated with depression and hypertension - Lin Meng; Dongmei Chen; Fei Pei; Rutai Hui; Yang Zheng; Jingzhou Chen (Clinical and Experimental Hypertension, 2017)
Objective: This study aims to detect the role of DNA methylation in norepinephrine transporter (NET) gene promoter region on the association between depression and hypertension. Methods: A total of 162 subjects were categorized into four groups based on depression scores and blood pressure. DNA was extracted from peripheral white blood cells and methylation levels of nine CpG sites in NET gene promoter region were investigated by pyrosequencing. Results: For each CpG site and the average value of nine CpG sites, there were no significant differences in DNA methylation of the NET gene promoter between healthy controls and patients with depression or hypertension. And there were no significant differences among groups after adjusting for age and body mass index. However, DNA methylation levels of the CpG sites adjacent to transcription start site tended to be low. In addition, CpG1.2–CpG5.2 were highly correlated with CpG4 as the first principle component, while CpG2 and the part of CpG1 and 3 were the second principle components. The total participants were clustered into three subgroups by hierarchical cluster analysis of methylated levels. Conclusion: Our study indicates that DNA methylation levels of nine CpG sites in NET gene promoter region are not associated with depression and hypertension.